Pengaruh Gaya Hidup, Label Halal, Kualitas Produk dan Harga Terhadap Keputusan Pembelian Kosmetik Wardah Pada Masyarakat Kecamatan Bilah Hilir - Maharani, Indah Setia (Universitas Labuhanbatu, 2021)
Currently with the development of science, culture and technology, the needs of human life is growing as well. The need to beautify themselves is now a top priority in supporting everyday appearance, especially cosmetics become a trend today. The competition between the personal care and cosmetics industry markets is increasingly competitive. This is evidenced by the many types of cosmetics of domestic production and foreign production that circulate well in Indonesia. So consumers should pay attention to the halal label and product quality of the cosmetic. This study aims to determine and analyze 1) the influence of lifestyle on purchasing decisions, 2) the influence of halal labels on purchasing decisions, 3) the influence of product quality on purchasing decisions, and 4) the influence of price on purchasing decisions, the population in this study is consumers in the downstream bar Kecataman who have bought and used Wardah Cosmetics and the sample in this study was taken using Slovin and obtained the number of samples as many as 100 people. The data analysis method used is validity and reliability test, classical assumption test, multiple regression analysis test , hypothesis test through T-test and f-test, determination coefficient test. Testing is done using the help of SPSS.Â The results showed that lifestyle variables partially showed t-count (4,041)> t-table (1,984) with GIS. Amounted to 0.027 which means lifestyle variables have a positive and significant effect on the purchase decision.Variable halal label partially, showing t-count (4,948)>t-table (1,984) with sig. Amounted to 0.032 which means the variable halal label has a positive effect and GIS. against the purchase decision. Product quality variable has partial effect, showing t-count (3,834)>t-table (1,984) with GIS. Of 0.006 which means the variable quality of the product has a positive effect and GIS. to the purchase decision, the price variable has a partial effect, showing t-count (3,462)>t-table (1,984) with GIS. Of 0.000 which means the price variable has a positive effect and GIS. on the purchase decision based on simultaneous testing (test - F), it is seen that f-count (39.478) > F-table (3.09) with a GIS of 0.000 which means lifestyle variables, halal label, product quality and price together have a positive effect and GIS. against the purchase decision. Analysis of the coefficient of determination seen from the value of R Square of 0.624 which means that the decision to purchase cosmetics Wardah at consumers in District Bar downstream can be met by lifestyle, halal label, product quality and price of 62.4% while the remaining 37.6% influenced by other factors that are not described in this study.